KONSISTENSI PEMERINTAH INDONESIA DALAM POLITICAL WILL PASCA KEIKUTSERTAAN RATIFIKASI PERJANJIAN INTERNASIONAL DI BIDANG HAM - Wahyu Nugroho (Jurnal Hukum, 2012)
Commitment or often termed the government's political will to implement and enforce the rights of the ratification of several international human rights instruments are still being encouraged and is a logical consequence of the ratification of human rights. At the national level, there are government programs through the National Action Plan human rights ideal, but at the regional / local, still going violations of human rights and the implementation of a slightly run due to differences in the interpretation of the meaning of human perception among law enforcement, people’s (civil society) and the government.In this study, the observed variables are: first, the consequences of the government's participation in the ratification of treaties on human rights, which is then transformed into national legislation. Here, researchers are more focused on the political will of the government, and second, people's perception of human rights before the government took part in the ratification of treaties on human rights and the changes are positive or merely lip service and political imagery alone.Approach or method that is applied using a socio-legal research or empirical legal research. Key informants of this research is the Head of the sub-directorate of economic, social, cultural and development at the Directorate General for Multilateral Directorate of Human Rights and Humanitarian Ministry of Foreign Affairs, Head of legal harmonization in the Directorate General of Human Rights of the Ministry of Law and Human Rights, Commissioner Assessment and Counseling sub Commission on Human Rights at the National Commission on Human Rights and Resource Development Deputy Head of Human Rights in ELSAM (Institute for Policy Research and Advocacy). Interviews using questionnaires and interviewKeywords : Political will, government, ratification, treaty, international human rights.